Climatic Variation: Effects on Stress Levels, Feed Intake, and Bodyweight of Broilers - Osti,R (2017)
ABSTRACT Chickens tolerate a very narrow range of climatic variation, and therefore, it is essential to determine the most suitable climatic area and weather for broiler production in open-house systems. In this study, 3060 broilers were used as experimental birds to investigate the effects of seasonal differences and climatic variations on the growth performance of broilers reared in an open-house system. Birds were kept under various treatment models that differ in climate Tropic zone, sub tropic zone and temperate zones. Data were recorded during July-August as summer months and January-February as winter months. Collected data was analyzed using the least square procedure given by Harvey-1990. Significantly higher (p<0.05) level of corticosteroids and H/L ratio of between the experimental birds was observed and consequent effect on feed intake was determined. The body weight and FCR at 42 day was significantly (p≤0.05) higher during winter season in subtropical zone. Subtropical climatic zone was found significantly better than other climatic zone. Efficient management of broiler farming that corresponds for effective feed intake during heat/cold stress to maximize bird’s efficiency can significantly increase production efficiency and acquiesce highest profit to broiler farming.